Contextualization: beyond the systemic narratives in favor of interdisciplinarity - Maycon Batista Leite; Márlon Herbert Flora Barbosa Soares (Investigações em Ensino de Ciências, 2021)
The narratives in favor of interdisciplinarity pervade through different perspectives from different theoritical-philosophical bases. There are interests from various sectors of society, in especial from the productive sector, which demand interdisciplinary projects. In formation or in performance, an interdisciplinary worker is demanded, linked to the current capitalist market. The present article asks about which of the approach perspectives of the scientific knowledge, interdisciplinarity or contextualization, can contribute more effectively with the logic that prioritizes human values over the capital. The idea is not the dichotomization but point out that the contextualization is the perspective that circumscribes the one of the interdisciplinarity when the objective is to form the critical subject in the apprehension of social reality. This perspective does not demand, inevitably, group or team projects, but the apprehension of the complex relationships between the scientific knowledge and the subject’s real-life process in society in the globalized and capitalist world, either through disciplinary or interdisciplinary knowledge. The contextualization is more associated to the transdisciplinarity than to the interdisciplinarity. The transdisciplinarity action is not a higher level of the interdisciplinarity, but a process that transcends the disciplinary and interdisciplinary views and perspectives in the process of approaching and understanding the social reality.